Environmental management tool kit for Caribbean hotels - Jones, Eleanor B (Caribbean Hotel Association [Santurce]PR, 1995)
Seeks to assist the Caribbean hotel owner and operator with practical steps toward making their properties more competitive in a global marketplace where the demand for environmentally friendly tourism services has increased rapidly.